Software development for examination of potential industrial application of commercial PC architecture - Molnár, S.; Lágymányosi, Attila; Tímár, T.; Dezső, O.; Szöllősi, Zs.; Tokai, Z. (Acta Agraria Kaposváriensis, 2006)
Applied computer is an essential element of control, based on artificial intelligence. Due to the rapid development of personal computers, nowadays PC-s considering their storage capacity and processing speed are suitable to control particular industrial processes. Several computer manufacturers construct PC-s and hardware components for uses under specially industrial circumstances. On limited climatic conditions commercial PC-s can be made suitable for application in industrial circumstances. It is worth mentioning that commercial PC-s and their components very different in reliability and climatic sensibility. So selecting parts of applied computers is important. On the other hand making tests under climatic conditions is also essential in filtering unusable units. For solving this problem a computer system is under development. Its basic function is to test hardware components from climatic point of view. The goal in this project is to design the hardware structure of the system, and develop a client-server application for controlling the whole process. This article is a brief introduction into this work containing the rough scheme of the system and making the server side software.
Keywords: control; test; software development; database